Geographic Data Access in an Ontology-based Peer Data Management System - Figueiredo, Rafael; Pitta, Daniela; Salgado, Ana Carolina; Souza, Damires (Journal of Information and Data Management, 2013)
In distributed data environments, ontologies have been used as a support for data management. For instance, ontologies may be used to describe the semantics of data at different sources, helping to overcome problems of data heterogeneity and semantic interoperability. Generally, the task of accessing data by means of conceptual ontologies has been called Ontology-based Data Access (OBDA). A typical scenario for OBDA instantiation is a Peer Data Management System (PDMS) where queries submitted at a peer are answered with data residing at that peer and with data acquired from neighbor peers through the use of mappings. In this work, we apply the principles underlying an ODBA in the light of a PDMS, using geographic databases as data sources. When dealing with geospatial data, specific problems regarding query answering and data visualization may occur. To help matters, we propose an approach named easeGO, which provides access to a geographic database using an ontology. We also present a tool, which allows users to formulate queries using the peer ontology as well as visual elements and spatial operators. We present the principles underlying our approach, examples illustrating how it works and some obtained experimental results.